Socially responsible human resource policies and practices: Academic and professional validation - Jesus Barrena-Martínez; Macarena López-Fernández; Pedro Miguel Romero-Fernández (European Research on Management and Business Economics (ERMBE), 2017)
This article addresses the measurement and validation of socially responsible human resource policiesfrom academic and professional points of view. Corporate Social responsibility (CSR) has made greatprogress in recent years in the theoretical realm, showing its importance through different perspectivessuch as the institutional theory, the stakeholder approach, the theory of legitimacy, and the process ofshared value. However, from an empirical standpoint, more research is needed to provide new indicatorsand evidence of testing socially responsible policies on business performance. This paper aims to devise aset of socially responsible human resource policies, demonstrate the validation of their content throughseveral practices, and review the analysis of their relative weights thanks to the contribution of a panelof academic experts and a professional pretest, conducted in large Spanish companies.
Keywords: M12; M14; 650; Corporate Social Responsibility; Human Resource Management; Panel of experts; Socially responsible policies